1972
DOI: 10.1039/p19720002563
|View full text |Cite
|
Sign up to set email alerts
|

Simple, convenient, and direct conversion of anilines and anilides into arynes

Abstract: EH9 3JJReaction of aniline with pentyl nitrite and acetic anhydride in benzene, or other solvents, gives benzyne in up to 32% yield as measured by trapping with anthracene, and tetraphenylcyclopentadienone and its 2.5-di-p-tolyl analogue. The role of the anhydride is to by-pass the suppressive effect of water on benzyne formation from the diazonium acetate ion pair. Reaction in benzene of aniline-acetic anhydride or (better) acetanilide with p-chlorobenzoyl nitrite (PCBN) (from silver p-chlorobenzoate and nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1973
1973
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Subsequently, report from Baigrie and co-workers claimed that substituted anilines and anilides were smoothly converted into substituted benzynes, followed by the application of the benzynes as dienophiles in DA cycloaddition to tetraphenylcyclopentadienone (or in some cases 2,-diphenyl3,4- p -tolylcyclopentadienone) with CO extrusion ( Scheme 227 ) [ 287 ].…”
Section: Cyclopentadienones For the Multisubstituted Benzene Ring And Naphthalene System Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, report from Baigrie and co-workers claimed that substituted anilines and anilides were smoothly converted into substituted benzynes, followed by the application of the benzynes as dienophiles in DA cycloaddition to tetraphenylcyclopentadienone (or in some cases 2,-diphenyl3,4- p -tolylcyclopentadienone) with CO extrusion ( Scheme 227 ) [ 287 ].…”
Section: Cyclopentadienones For the Multisubstituted Benzene Ring And Naphthalene System Formationmentioning
confidence: 99%
“… Synthesis of tetraphenylnaphthalene derivatives via cycloaddition of substituted benzynes to tetraphenylcyclopentadienone [ 287 ]. Reagents and conditions: X = H or COOMe; Y = H, F, Cl, Br, I, Me, t -Bu, and other substituents in various position.…”
Section: Figure and Schemesmentioning
confidence: 99%
“…5-(Trifluoromethyl)-1,2,3,4-tetraphenylnaphthalene (3l) 15 . mp 178-180 uC; 1 H NMR (500 MHz, CDCl 3 ): d: 8.01 (d, J = 7.0 Hz, 1H), 7.89 (d, J = 8.5 Hz, 1H), 7.44 (t, J = 8.0 Hz, 1H), 7.30-7.08 (m, 10H), 6.90-6.73 (m, 10H); 13 C NMR (125 MHz, CDCl 3 ): d: 142.…”
Section: General Procedures For the Pd Catalyzed Annulation Reactionmentioning
confidence: 99%
“…It has been observed that the ortho and para substituted aryl bromides reacted with diphenylacetylene to provide only one product. In case of meta substituted aryl bromides (Table 2,entries 3,4,6,9,15,17,and Table 3, entry 2) a small amount of the isomeric product (5-10%) was also formed. Again, the heteroaryl bromides or iodide (Table 3, entries 6, 7 and 9) furnished only one regioisomer.…”
Section: Introductionmentioning
confidence: 99%
“…5,7-Dimethyl-1,2,3,4-Tetraphenylnaphthalene (4i) (entry 4 in Table 4): mp 251-257 o C (lit. 25 mp 249 o C); 1 H NMR (270 MHz, CDCl 3 ): d 1.92 (s, 3H), 2.30 (s, 3H), 6.71-6.84 (m, 10H), 7.05-7.22 (m, 11H), 7.28 (s, 1H); 13 C NMR (67.8 MHz, CDCl 3 ): d 21.6, 25.3, 124.8, 125.0, 125.1, 126.0, 126.1 (overlapped), 126.3, 126.7, 127.3, 129.1, 131.0, 131.2, 131.3, 131.5, 132.5, 133.5, 134.8, 135.5, 137.8, 138.3, 138.4, 139.4, 140.3, 140.7 (overlapped), 142.9; MS m/z 460 (M + ).5-Chloro-1,2,3,4-Tetraphenylnaphthalene (4j)24 (entry 5 in Table4) (as a mixture with 4c (4j:4c = 3:1)): 1 H NMR (270 MHz, CDCl 3 ): d 6.72-6.89 (m, 10H), 6.72-6.89 (m, 10H, 4c), 7.05-7.27 (m, 11H), 7.05-7.27 (m, 10H, 4c), 7.31 (dd, J = 9.1, 2.1 Hz, 1H, 4c), 7.51 (dd, J = 7.4, 1.3 Hz, 1H), 7.57 (d, J = 8.9 Hz, 1H, 4c), 7.58 (dd, J = 8.4, 1.3 Hz, 1H), 7.61 (d, J = 2.1 Hz, 1H, 4c);13 C NMR (67.8 MHz, CDCl 3 ): d 125.1, 125.3, 125.4, 125.6, 126.0, 126.2, 126.45, 126.51, 126.6, 127.0, 127.48, 127.52, 127.6, 127.8, 128.4, 128.7, 129.7, 129.8, 130.3, 130.8, 131.05, 131.09, 131.4, 131.85, 131.88, 134.5, 136.9, 138.7, 138.9, 139.0, 139.1, 139.5, 140.0, 141.1, 141.7; MS m/z 466, 468 (M + ).…”
mentioning
confidence: 99%